Hematological Inflammatory Indicators in Women with Gestational Diabetes - Mohammad Hossein Ahmadi; Mohsen Maleknia; Mohammad Reza Javan; Mehrnaz Abdolalian; Fatemeh Golshahi; Elham Vahabi (Mashhad University of Medical Sciences, 2022)
Introduction: Given the role of chronic inflammation in developing GDM (gestational diabetes mellitus), investigating hematological inflammatory indicators such as platelet-to-lymphocyte ratio (PLR), hemoglobin-to-platelet ratio (HPR), and other blood biomarkers can be helpful in GDM patients. The present study was conducted aimed to evaluate the hematological inflammatory indicators of women with GDM compared to the control group. Methods: In this retrospective study, the profiles of 300 pregnant women with a definite diagnosis of GDM admitted to Mohebbe Yas Hospital (Tehran) from 2019 to 2021 were investigated. In this study, the absolute number of blood cells and other hematological parameters were evaluated in separate groups of diabetic and normal pregnant mothers. The sensitivity and specificity of each statistically significant variable were determined by ROC curve analysis. Data were analyzed by SPSS (version 22) and Mann-Whitney U, Independent t-test, Wilcoxon, and Chi-square tests. P˂0.05 was considered statistically significant. Results: In terms of absolute lymphocyte count (ALC), the results of comparison between GDM and normal groups showed that this index had a sensitivity of 84.07% and a specificity of 37.98% in the diagnosis of GDM patients, and it was statistically significant (p= 0.022). The absolute neutrophil count (ANC) index had a sensitivity of 66.78% and a specificity of 53.49%, which was statistically significant (p= 0.012). The PLR index had a sensitivity of 54.08% and a specificity of 66.67% (p<0.001). However, HPR and NLR indices were not statistically significant (p>0.05). Conclusion: This study showed that in GDM patients, ALC and ANC indices decrease and PLR increases. To improve the screening process of high-risk pregnant women for GDM, the predictive value of each of these indices in the incidence of GDM can be investigated in future studies.